Tribology Investigation of Automotive Air Condition (AAC) Compressor by using Al2O3/PAG Nanolubricant - Aminullah, A. R. M.; Azmi, W. H.; A. A. M., Redhwan; M. Z., Sharif; Nurul Nadia, Mohd Zawawi; K., Kadirgama; M. N. S., Ashraf (Faculty of Mechanical Engineering, Universiti Teknologi MARA (UiTM), Malaysia., 2018)
Lubrication is a requisite for any mechanical equipment that moved to avoid wear of sliding parts and enhance the equipment operation consistency. The objective of this study was to seek a new improved automotive air conditioning (AAC) compressor lubricant to enhanced AAC performances. The type of compressor is piston type, Sanden SD 7H10, that normally used by Malaysia compact car. The tribological investigation was focusing on Coefficient of friction and wear rate. The wear rate and coefficient of friction (COF) of Alumina/Polyalkylene glycol (Al2O3/PAG) nanolubricant were evaluated employing reciprocating test conditions to replicate a piston ring/cylinder liner contact following the ASTM G 181-11 Standard. Al2O3 nanoparticle was dispersed in PAG lubricant for volume concentrations between 0.006 to 0.014 vol %. Al2O3/PAG nanolubricant with 0.010 % vol. concentration showed the best reduction of frictional power loss. The enhancement of power saving due to frictional losses was up to 7.59 % compared to pure PAG lubricant.